Smartphone Usage by Expert Blind Users - Jain, Mohit; Diwakar, Nirmalendu; Manohar, Swami (CHI Conference on Human Factors in Computing Systems (CHI’21), 2021)
People with vision impairments access smartphones with the help of screen reader apps such as TalkBack for Android and VoiceOver for iPhone. Prior research has mostly focused on understanding touchscreen phone adoption and typing performance of novice blind users by logging their real-world smartphone usage. Understanding smartphone usage pattern and practices of expert users can help in developing tools and tutorials for transitioning novice and intermediate users to expert users. In this work, we logged smartphone usage data of eight expert Android smartphone users with visual impairments for four weeks, and then interviewed them. This paper presents a detailed analysis that uncovered novel usage patterns, such as extensive usage of directional gestures, reliance on voice and external keyboard for text input, and repurposed explore by touch for single-tap. We conclude with design recommendations to inform the future of mobile accessibility, including hardware guidelines and rethinking accessible software design.